2014
DOI: 10.4161/cbt.28875
|View full text |Cite
|
Sign up to set email alerts
|

Etoposide-loaded immunoliposomes as active targeting agents for GD2-positive malignancies

Abstract: Systemic chemotherapeutics remain the standard of care for most malignancies even though they frequently suffer from narrow therapeutic index, poor serum solubility, and off-target effects. In this study, we have encapsulated etoposide, a topoisomerase inhibitor effective against a wide range of cancers, in surface-modified liposomes decorated with anti-GD2 antibodies. We characterized the properties of the liposomes using a variety of methods including dynamic light scattering, electron microscopy, and Fourie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…Because of an evident expression of GD2 on NB cells surface and role in NB pathogenesis and progression, it potentially serves as a target in NB therapy (Saito et al, ; Yang & Sondel, ). GD2 has been utilized as a target in monoclonal antibody therapy and has been the primary target of antibody recognition in NB (Brown, ; Kushner et al, ; Thurin et al, ). Various researches demonstrated that normal tissue in brain only expression GD2 where is inaccessible to circulating antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Because of an evident expression of GD2 on NB cells surface and role in NB pathogenesis and progression, it potentially serves as a target in NB therapy (Saito et al, ; Yang & Sondel, ). GD2 has been utilized as a target in monoclonal antibody therapy and has been the primary target of antibody recognition in NB (Brown, ; Kushner et al, ; Thurin et al, ). Various researches demonstrated that normal tissue in brain only expression GD2 where is inaccessible to circulating antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, newly developed different liposomal combinations/formulations and liposomal vaccines have shown promising results in clinical studies and in commercial applications. In all, liposomal formulations are still important and potential tool for its clinical application of nanomedicines [45,50,61,63,65,.…”
Section: Discussionmentioning
confidence: 99%
“…Disialo-ganglioside GD-2 is a tumor marker expressed in many cancers and targeting cancer cells by antibodies against GD2 is a major strategy employed in cancer therapy [44]. Immuno-liposomes coated with anti-GD2 antibody, encapsulating anticancer drug etoposide targeting GD2 expressing cancer cells, has been reported to enter targeted cells via clathrin-coated pits, thereby causing reduction in cell proliferation in in-vitro studies and offers advantage over conventional chemotherapeutics in specific cancer cell targeting [45].…”
Section: Cancer Targetingmentioning
confidence: 99%
“…Surface-functionalized liposomes with antibodies decreased steric hindrance during targeting, facilitating binding of liposomes to cancer cells. 51 Anti-EphA10 is expressed in all subsets of breast cancer but is not expressed in normal breast tissue. 52 Nagano et al 53 revealed that the administration of an anti-EphA10 antibody significantly suppressed tumor growth in a xenograft mouse model, indicating anti-EphA10 as the target for breast cancer.…”
Section: In Vitro Cellular Uptake Of Epslrmentioning
confidence: 99%